The Workplace wellbeing dan employee engagement pada karyawan: Menguji peranan resiliensi sebagai mediator: Workplace wellbeing and employee engagement in employees: Examining the role of resilience as a mediator - Dewi, Ros Patriani; Wardhani, Nia Kusuma (Persona:Jurnal Psikologi Indonesia, 2023)
The existence of globalization encourages every organization to be more adaptive in facing dynamic changes. Employee engagement is considered one of the important factors that can increase human resource performance. This research aimed to understand the impact of variables that can influence employee engagement, in order for the employees can be more engaged to the organization. Furthermore, this study examined the relationship between workplace well-being toward employee engagement with resilience as a mediator. The method used in this research was the quantitative method. The questionnaires using a random sampling technique and the answers from 183 employees across various regions in Indonesia with the following characteristics: employees aged 20 to 50, minimum tenure 1 year, were analyzed using SEM (Structure Equation Modelling) with the assistance of the smart PLS program. According to the analysis, it was found that (1) workplace wellbeing positively significantly influences employee engagement, (2) workplace wellbeing positively significantly influences resilience, (3) resilience positively significantly influences employee engagement, and (4) resilience mediates the relationship between workplace wellbeing and employee engagement. The result indicates that an Organization can increase employee engagement by building strong workplace well-being and supporting employees in increasing their resilience.